Fromm’s Concept of Man and the Possibilities of His Authentic Life in Society (Part I) - Jekentaitė, Leonarda (Problemos, 1980)
Ideological significance of the investigation of the philosophy of Neo-Freudism lies in the fact that Neo-Freudism considers the introduction of psychoanalysis into Marxism. Critical analysis of the concept of the nature of man and the treatment of his individuality in Fromm's philosophy renders sufficient testimony for the author of the present paper to disclose the subjectivism of this theory. The first part of the present paper is concerned. with the critical analysis of Fromm’s interpretation of the Marxist concept of the nature of man.